The gastropod community structure of the Lukut mangroves, Negeri Sembilan / Nur Anis Fadilah Sukeri - Sukeri, Nur Anis Fadilah (2016)
This study reports on the distribution, abundance, community structure, morphometric relationship of mangrove gastropods from Sungai Lukut, Negeri Sembilan sampled from February to May 2015. The line transect with quadrat method was employed to sample the gastropods which were handpicked within quadrat (5m x 5m) from the root, stem, branch, floor and where possible leaves. Water physicochemical parameters namely dissolved oxygen, temperature, salinity and pH were measured in situ. Thirty six species of gastropod taxa from 13 families were recorded from 4 mangrove sampling sites (coastal and river mouth, fringing riverine, intact riverine and upstream). Rhizophora apiculata (1314 ind/hectare) and Sonneratia alba (750 ind/hectare) were the most represented among the mangrove trees while Littoraria scabra (1.219 ind/m2) and Nerita lineata (1.109 ind/m²) were the most abundant gastropod species sampled. Higher species richness (S = 0.99) of mangrove trees was recorded at the upstream mangroves while higher species diversity (H' = 0.31) and evenness index (JH = 0.28) of mangrove trees were recorded at the coastal and river mouth mangroves. For gastropod taxa, S = 1.81 was noted higher at the upstream mangroves while FT = 0.29 and J' = 0.26 of gastropod species sampled indices high species diversity and evenness index at the fringing riverine mangroves. The regression of shell length and weight showed positive allometric (Columbella duclosiana), negative allometric (Sphaerassiminea miniata and Cerithidea obtusa) and isometric {Littoraria melanostoma, Littoraria conica and Drupa margariticola) growth for the gastropods.